Answer: -6
Explanation:
If x:(x+3) = 2:3, we can set up the following equation:
x / (x+3) = 2/3
Next, we can multiply both sides of the equation by 3 to get rid of the fraction on the right side:
3 * (x / (x+3)) = 3 * (2/3)
This gives us:
x / (x+3) = 2
Finally, we can multiply both sides of the equation by (x+3) to get rid of the fraction on the left side:
x = 2 * (x+3)
We can then solve for x by rearranging the terms on the right side of the equation:
x = 2x + 6
Subtracting 2x from both sides gives us:
x - 2x = 6
This simplifies to:
-x = 6
Finally, we can divide both sides of the equation by -1 to solve for x:
x = -6
Therefore, x = -6.